An Examination of Potential Misclassification of Army Suicides: Results from the Army Study to Assess Risk and Resilience in Servicemembers. Issue 3 (22nd July 2016) - Cox, Kenneth L.; Nock, Matthew K.; Biggs, Quinn M.; Bornemann, Jennifer; Colpe, Lisa J.; Dempsey, Catherine L.; Heeringa, Steven G.; McCarroll, James E.; Ng, Tsz Hin; Schoenbaum, Michael; Ursano, Robert J.; Zhang, Bailey G.; et al.
Abstract : Debate continues about the accuracy of military suicide reporting due to concerns that some suicides may be classified as accidents to minimize stigma and ensure survivor benefits. We systematically reviewed records for 998 active duty Army deaths (510 suicides; 488 accident, homicide, and undetermined deaths; 2005‐2009) and, using research criteria, reclassified 8.2% of the nonsuicide cases to definite suicide (1), suicide probable (4), or suicide possible (35). The reclassification rate to definite suicide was only 0.2% (1/488). This low rate suggests that flagrant misclassification of Army deaths is uncommon and surveillance reports likely reflect the "true" population of Army suicides.